UMOWA KOMENDY W ŚREDNIOWIECZU - Rafał Wojciechowski (Zeszyty Prawnicze)
T h e C o m m e n d a C o n t r a c t in t h e M i d d l e A g e s Summary The author of this article deals with the commenda contract in the Middle Ages. First of all he characterized the most important features of the commenda contract in Italy, because in this country it appeared already in the 10th century. One kind of the commenda contract was one-sided. The contract of this kind consisted in an agreement, in accordance with which one party invested some capital and the other contributed his enterprise. The liability of the partner who invested capital was limited only to its amount. Differently from the modern continental Kommanditgesellschaft or société en accommandite, in the one-sided contract the active partner was not liable for possible losses. This feature of the contract was connected with the fact that commenda was made for a single trade expedition, in which the risk of loss concerned the invested capital only. In the mutual commenda the partner who put into commenda the enterprise made his own material contribution which enlarged his share in the profits.